Use of Websites in School Management: An Effort to Build School Readiness in the Era of 4.0 - Saidah Laugi (Institut Agama Islam Negeri (IAIN) Kendari, 2020)
This article provides an overview of several aspects related to websites, which include: first, understanding the website; second, the criteria for a good and quality website; third; the benefits of the website for educational institutions; fourth, a web-based school information system; fifth, school web development in learning activities; and sixth, the basic principles of school web management. This study was conducted using the library method, where the author collects various materials such as books and scientific articles, which are further elaborated to obtain a broader and deeper understanding of the use of websites in school management. The results of the study show that: first, it is a very complex device because it combines various domains through the internet network, resulting in complex data in the form of text, images, video, audio, and animation. Second, a good school website must meet the following criteria: easy, navigation structure, graphic design, content, compatible, fast, functional, accessible to everyone, and interactive. Third, the school website is an important tool in school management, not only internally but also externally. Fourth, the impact of IT advances has reached various areas of life, so schools should have web-based information systems. Fifth, the school web must be developed in the school's main business domain, namely education and learning. Sixth, to ensure the occurrence of web-based school management, the basic principles of school web management must be carried out properly. Keywords: School Management, ICT, Website, Quality